Entrepreneurial marketing and marketing performance through digital marketing capabilities of SMEs in post-pandemic recovery - Zakiyah Zahara; Ikhsan; Ira Nuriya Santi; Farid (Cogent Business & Management, 2023)
AbstractThe use of digital resources through digital marketing is an option to be able to reach customers, build interactions with customers in real time and finally achieve customer satisfaction. This research intends to determine the influence of entrepreneurial marketing through digital marketing capabilities on marketing performance in Palu, Indonesia. The population in the study amounted to 21,696 with a total number of samples of 197 SMEs obtained with the Yamane and Isaac formula. The sampling technique in this study went through two stages, namely the Area Sampling Technique and then the Stratified Random Sampling Technique. Hypothesis testing used was path analysis with Smart-PLS software. The results showed that entrepreneurial marketing have positive and significant effects on digital marketing capabilities and on marketing performance. Furthermore, digital marketing capabilities have a positive and significant effect on marketing performance. However, digital marketing is less likely to mediate the relationship between entrepreneurial marketing and marketing performance. As practical implications, SMEs should continue to improve their capabilities and sharpen the implementation of entrepreneurial marketing strategies, in order to utilize their resources to find opportunities and create added value for customers, in order to continue to achieve marketing performance in a sustainable manner.